A Five-Year Review on Pediatric Foreign Body Aspiration - Nasir,Zuraini Mohammad (2021)
Abstract Introduction Foreign body aspiration is a leading cause of accidental death in children. Clinical presentation varies from non-specific respiratory symptoms to respiratory failure making diagnosis challenging. Objective To review pediatric patients who underwent bronchoscopy due to suspicion of foreign body aspiration at a tertiary center in Malaysia. Methods We retrospectively studied patients > 11 years old who underwent bronchoscopy from 2008 to 2018. Results Over the 10-year period, 20 patients underwent bronchoscopy, and 16 were found to have foreign body aspiration with equal gender distribution. The most common age group was > 3 years old (75%). The most common clinical presentations were choking (82%) and stridor (31%). Foreign bodies were removed using flexible bronchoscope in 8 cases (50%), and difficulties were encountered in 6 cases (75%). Rigid ventilating bronchoscope was used in 8 cases (50%) with no difficulty. The most common object found was peanut (19%). The majority of foreign bodies were lodged in the right bronchus (43%). Eight patients (80%) received delayed treatment due to delayed diagnosis. The length of hospital stay was longer in the younger age groups. Conclusion Clinical presentation and chest radiograph findings were comparable across all age groups. The most difficulties encountered during foreign body removal were via flexible bronchoscope, in children > 3 years old. There was no significant correlation between age and type of foreign body aspiration. The majority of patients who received delayed treatment were > 3 years old. The length of hospital stay was longer in the younger age groups.